Hybrid Short-Term Wind Power Prediction Based on Markov Chain - Zhou, Liangsong; Zhou, Xiaotian; Liang, Hao; Huang, Mutao; Li, Yi (Frontiers in Energy Research, 2022)
This paper proposes a combined prediction method based on the Markov chain to improve the precision in short-term wind power prediction. First, three chaotic models are proposed for the prediction of chaotic time series. Then, the proposed model combining these three models with weights calculated by a Markov chain is constructed. Finally, the industrial data from a Chinese wind farm is taken as a study case, and its results validate the feasibility and superiority of the proposed prediction method